PELAKSANAAN PERATURAN MAHKAMAH AGUNG NOMOR 4 TAHUN 2019 TENTANG PERUBAHAN ATAS PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2015 TENTANG TATA CARA PENYELESAIAN GUGATAN SEDERHANA DI PENGADILAN NEGERI PEKANBARU - Arifin, Rizki Haidir; Bachtiar, Maryati; Darnia, Meriza Elpha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Supreme Court Regulation Number 4 2019 the change of Supreme Court Regulation Number 22015 about Small Claim Court Implementation Procedure regulate about small claim court mechanismfrom the case received by court until the call for the defendant to implement the decision or called byaanmaning, in the case number 37/pdt.g.s/2021/PN.Pbr and 27/pdt.g.s/2023/PN.Pbr there few thingsthat couldn’t applicated according to the regulation, there is the maximal time to finish the lawsuit andthe maximal time to determine aanmaning, the purpose of this research is to know how theimplementation and the obstacle of Supreme Court Regulation Number 4 2019 the change of SupremeCourt Regulation Number 2 2015 about Small Claim Court implementation procedure in PekanbaruDistrict court.Type of research used is empirical research and is supported by literature studies, the authordirectly conducted research on the location to provide a clear picture of the problem being studied. Thisresearch was conducted at the Pekanbaru District Court, the sample population in this study was Mr.Jon Kenedi as representative of the plaintiff's attorney, Mr. Boyke Amri as representative of thedefendant's attorney, Mr. Salomo Ginting and Mr. Sugeng Harsoyo as Judge of the Pekanbaru DistrictCourt, Mr. Sutanto as Registrar of the Pekanbaru District Court, data sources used, primary data andsecondary data, data collection techniques in this research using interviews, literature review and dataanalysisThe results of research on problems regarding the implementation of Supreme Court Regulation4 of 2019 can be concluded that the implementation of Supreme Court Regulation Number 4 of 2019 atthe Pekanbaru District Court has actually reduce the accumulatiion case, there are several provisionsthat have not been implemented in accordance with the Supreme Court Regulation which is caused by anumber of internal inhibiting factors. namely limited time and external, namely the absence of the partiesat the first hearing. Therefore the judges as the implement of the regulation need to know what is theobstacle of the implementation Supreme Court Regulation in Pekanbaru District Court to solve theunsuitable application of Supreme Court Regulation, and the party who involved in the determine ofaanmaning should pay attention to more details regarding the timing of the aanmaning determinationand the purpose formed of Supreme Court Regulation Number 4 2019 The Change of Supreme CourtRegulation Number 2 2015 about Small Claim Court Implementation Procedure can be achieved.Keywords: Small Claim Court-Supreme Court Regulation-Implementation.